SELF-ESTEEM, PEER INFLUENCE AND SOCIAL MEDIA UTILISATION AS CORRELATES OF READING HABIT OF SENIOR SECONDARY SCHOOL STUDENTS IN OYO STATE, NIGERIA (2015)
The reading habit of secondary school students in Nigeria has been found to be on the decline. This trend can be traced to lack of library infrastructure and facilities in most schools and homes. This has raised concern among stakeholders and portends danger for the academic performance. Previous studies have focused more on home- and school-related factors with little emphasis on students-related factors such as selfesteem, peer influence and social media utilisation. This study, therefore, examined the extent to which self-esteem, peer influence and social media utilisation correlated with the reading habit of secondary school students in Oyo State, Nigeria. The study adopted survey design. Eighteen Local Government Areas (LGAs) were randomly selected across the three senatorial districts of the state. Eight senior secondary schools (4 public; 4 private) were randomly selected from each of the 16 out of the 18 LGAs used; while six schools (4 public; 2 private) were selected from each of the two remaining LGAs. The stratified random sampling technique was adopted in selecting 2,468 senior secondary II students across the 140 schools used for the study. Four scales were used for data collection: Self-esteem (α=0.79), Peer Influence (α=0.75), Social Media Utilisation (α=0.76) and Reading Habit (Purpose: α=0.80, Mannerism: α=0.75, Pattern: α=0.70, Types: α=0.65, Frequency: α=0.79) scales. Data were analysed using percentages, Pearson moment correlation and multiple regression at 0.05 level of significance. Reading to pass examinations (68.4%), self-development (66.7%), acquisition of information (61.1%), leisure and fun-seeking (58.3%), desire to be at par with mates (54.2%) and while away time (52.6%) were purposes for reading. Coffee-taking (47.6%), soaking legs in water (38.4%), drug usage (36.6%), gum chewing (35.1%), listening to music (34.5%) and biting finger nails (33.0%) were done alongside with reading. Reading frequencies among the students were: less than one hour (53.8%), 2 - 4 hours (49.7%), one hour (40.1%), 4 - 6 hours (38.9%), and 6 hours and above (32.6%). Self-esteem, peer influence, and social media utilisation jointly contributed to the reading habit senior secondary II students (F(3,2464)=111.17) and accounted for 12.0% of its variance. Social media utilisation (β=0.32) and peer influence (β=0.06) had significant relative contribution to reading habit while self-esteem did not. Social media utilisation (r=0.34), peer influence (r=0.19) and self-esteem (r=0.16) had significant correlations with reading habit. There was a significant difference (t=2.53; df=2466) in the reading habit of students in private ( x =99.50) and public ( x =95.63) schools. Students‟ self-esteem, peer influence and social media utilisation influenced reading habit among senior secondary school students in Oyo State, Nigeria. Therefore, concerted effort should be made to encourage the students to increase their reading hours with less emphasis on induced reading to pass examinations. In addition, educational agencies and social media service providers should intensify awareness on positive reading habit among senior secondary school students. Keywords: Peer influence, Reading habit of senior secondary school students in Oyo State, Social media utilisation. Word count: 463